2015
DOI: 10.3109/13880209.2015.1025287
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the catecholaminergic system on the antidepressant-like effects ofAlpinia zerumbetin mice

Abstract: Conclusion: These results indicated that HEA most likely acts through the dopaminergic and/or noradrenergic system but not through the serotoninergic or glutamatergic systems. This study reinforces the idea that the available biodiversity in Brazil can serve as a basis for innovation in the development of new drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…AMPT pretreatment (100 mg/kg) has been reported to reduce norepinephrine and dopamine levels by 53% and 57%, respectively, in the brains of mice without affecting serotonin levels (Mayorga et al, 2001; Widerlöv and Lewander, 1978). In this study, AMPT pretreatments did not alter the immobility time of control animals in parallel with the results of the previous studies (Bevilaqua et al, 2016; Can et al, 2013, 2017; Kwon et al, 2010; Pałucha-Poniewiera et al, 2017). However, it abolished the anti-immobility effect of tofisopam in the TST (Figure 3(b)), indicating that the catecholaminergic system, together with the serotonergic system, mediates the antidepressant-like effect of the drug.…”
Section: Discussionsupporting
confidence: 91%
“…AMPT pretreatment (100 mg/kg) has been reported to reduce norepinephrine and dopamine levels by 53% and 57%, respectively, in the brains of mice without affecting serotonin levels (Mayorga et al, 2001; Widerlöv and Lewander, 1978). In this study, AMPT pretreatments did not alter the immobility time of control animals in parallel with the results of the previous studies (Bevilaqua et al, 2016; Can et al, 2013, 2017; Kwon et al, 2010; Pałucha-Poniewiera et al, 2017). However, it abolished the anti-immobility effect of tofisopam in the TST (Figure 3(b)), indicating that the catecholaminergic system, together with the serotonergic system, mediates the antidepressant-like effect of the drug.…”
Section: Discussionsupporting
confidence: 91%
“…All behavioural tests were videotaped and quantified by an animal movement analysis system (SMART, Panlab SL, Barcelona, Spain). The behavioural tests used are well established 2 , 4 , 14 , 52 54 . The experimental timeline and study design are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Segundo Xuan e Teschke (2015), 5,6-Dehidrokawain (DK) e dihidro-5,6dehidrokawain (DDK) (Figura 1) são os principais constituintes de AZ sendo os responsáveis pelas propriedades terapêuticas da espécie (XUAN e TESCHKE, 2015). No entanto, existem outros compostos como Kaempferol-3-O-β-D-glucuronide (KOG), labdadieno, 2,5-bis(1E, 3E, 5E)-6-metoxihexa-1,3,5-trien-1-il)-2,5-di-hidrofurano (MTD), (E)-2,2,3,3-tetrametil-8-metileno-7-(oct-6en-1-il) octa-hidro-1H-quinolizina(TMOQ), pinostrobina (PTB), (E)-5-metoxi-8-(4-metoxi-2-oxo-2Hpiran-6-il)-7-fenil-1-estiril-2oxabiciclo[4.2.0]oct-4-en-3-1 (AS-2), tepinen-4-ol, 1,8-cineol e γ-cadinol, hispidina (H) e seus derivados (H1-H3) que também foram avaliados como possíveis compostos ativos para as atividades da AZ na última década (Figura 1) (NGUYEN et al, 2014;MENDES et al, 2015; TAIRA; NGUYEN e TAWATA, 2017; ROMAN JUNIOR et al, 2017;SHAHINOZZAMAN et al, 2018 (BEVILAQUA et al, 2016). Mas apesar dos avanços quanto a ação dos derivados da AZ, é importante destacar a necessidade de mais estudos para confirmar quais os possíveis transportadores e receptores envolvidos no seu efeito antidepressivo e ansiolítico e elucidar seus respectivos mecanismos de ação.…”
Section: Caracterização Fitoquímicaunclassified
“…Segundo Correa, Lima e Costa (2010) estudos publicados até 2008 avaliaram e, na maioria dos casos, comprovaram a atividade antimicrobiana, anticâncer, antioxidante, anti-hipertensiva, diurética e antinociceptiva de óleos essenciais, extratos e compostos isolados extraídos de partes dessa planta (CORREA; LIMA; COSTA, 2010). Contudo, a evolução da ciência na última década se deu de forma exponencial, promovendo o aperfeiçoamento de métodos de extração e isolamento, auxiliando assim, no desenvolvimento de estudos relacionados às vias de sinalização envolvidas nas atividades biológicas já conhecidas da AZ e na descoberta de novas, tais como atividade ansiolítica e antidepressiva (BEVILAQUA et al, 2016;ROMAN JUNIOR et al, 2017;SATOU et al, 2010). Assim, nesta revisão encontram-se pesquisas publicadas na última década (2010-2020) trazendo atualizações sobre os principais estudos quanto as atividades biológicas da AZ com discussão dos potenciais terapêuticos dessa espécie tão comum na região Nordeste.…”
Section: Introductionunclassified